SEISMIC ANALYSIS SYSTEM OF BRIDGE PIER WITH PILE FOUNDATION IN ARIAKE SOFT CLAY REGION - R. Mahmudur; G. Aramaki; Koga Katsuki; T. Ohtsuka (Lowland Technology International, 2002)
In our earlier paper which appeared in IALT, it is pointed out that design of bridge pier with big seismic loading needs special attention such as consideration of ground displacement, soil-pile interaction effect etc., when foundation pile penetrate through soft clay layer and ground displacement largely depends on soil shear wave velocity, Vs & strain dependence of G/G0. The Road Bridge Code in Japan states that shear wave velocity, Vs can be considered 50 m/sec in soft clay having SPT N-value zer. In this study, seismic analysis was carried out considering three cases: Case I using measured Vs value, Case II where Vs = 50 m/sec for all layers and Case III where Vs is calculated from the Railway Bridge Standard in Japan formula for the soft clay layer. Both of Penzien model and single input model analysis were performed. The bridge structure used in the analysis was first designedby Seismic Co-efficient Method and Ductility Design Method. In dynamic analysis, non-linear clasto-plastic material behavior was considered for piles. Lincar pile behavior case was also performed. In the former case rensponses mainly displacement and bending moment were found less compared to linear case. Responses in Case II were found much higher than other two cases and would result very uneconomical design. Penzien model analysis system, with non-linear pile material consideration is proposed for analysis of bridge pier with pile foundation in Ariake soft clay region. It is emphasized that Vs and also strain dependence of G/G0 be precisely measured in the soft clay region because of their big influence in seismic analysis in soft clay region. Difference between responses in Case I and Case III were found small. In the unavailability of measured data Vs may be calculated by the Railway Bridge Standard formula.